Pengaruh Variasi Durasi Waktu Injeksi Oksigen Terhadap Performansi Insinerator Dual Chamber Limbah Medis - Darma, I Wayan Arya; Winaya, I Nyoman Suprapta; Pratama, I Putu Angga Yuda; Sanatana, I Ketut Sakya (Fakultas Teknik UMSU, 2025)
Incineration is an effective waste processing method, especially for medical waste which is B3 waste. The high temperature combustion process in incineration is expected to be able to reduce medical waste optimally. However, emissions produced during the incineration process can pollute the surrounding environment and harm health. So it is necessary to develop incineration methods to reduce exhaust emissions but still be able to reduce medical waste optimally. In this research, additional oxygen injection was carried out in chamber 2 of the dual chamber medical waste incinerator by varying the duration of the oxygen injection time with the aim of obtaining optimal performance and reducing the resulting exhaust emissions. The research was carried out using medical waste weighing 1 kg with variations in the duration of oxygen injection, 2, 3 and 4 minutes. The research results show that increasing the duration of oxygen injection time can increase combustion efficiency, increase the temperature in chamber 2 and reduce the resulting exhaust gas emissions.